2000
DOI: 10.1002/1529-0131(200005)43:5<978::aid-anr4>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Rofecoxib, a specific inhibitor of cyclooxygenase 2, with clinical efficacy comparable with that of diclofenac sodium: Results of a one-year, randomized, clinical trial in patients with osteoarthritis of the knee and hip

Abstract: for the ROFECOXIB PHASE III PROTOCOL 035 STUDY GROUP Objective. To compare the clinical efficacy of rofecoxib, a specific inhibitor of cyclooxygenase 2 (COX-2), with that of diclofenac in patients with osteoarthritis (OA) and to evaluate the safety and tolerability of rofecoxib.Methods. We performed a randomized, doubleblind, active comparator-controlled trial in 784 adults with OA of the knee or hip. Patients were randomized to 1 of 3 treatment groups: 12.5 mg of rofecoxib once daily, 25 mg of rofecoxib once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(106 citation statements)
references
References 27 publications
1
103
0
2
Order By: Relevance
“…The summary risk of bias was 'low' for three studies, [88][89][90] 'moderate' for 13 studies and 'high' for one study. 85 Randomisation sequence was often described as computer generated, and details of stratification were often provided.…”
Section: Study Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…The summary risk of bias was 'low' for three studies, [88][89][90] 'moderate' for 13 studies and 'high' for one study. 85 Randomisation sequence was often described as computer generated, and details of stratification were often provided.…”
Section: Study Qualitymentioning
confidence: 99%
“…Only three trials reported using a method of randomisation where allocation concealment could be assessed by the reviewers as 'adequate'. [88][89][90][91] Baseline characteristics appeared comparable in 14 studies, unclear in two studies and did not appear comparable in one study.…”
Section: Study Qualitymentioning
confidence: 99%
“…The COX-2 inhibitors rofecoxib and celecoxib, or coxibs, are part of a new group of agents that have an antiinflammatory effect similar to that of NSAIDs and have been found to be as effective as these drugs in reducing pain and inflammation (11)(12)(13)(14)(15)(16)(17)(18)(19). Clinical trials have demonstrated that coxibs have a low potential for causing upper GI injury compared with NSAIDs (11,15-17,19 -21).…”
Section: Introductionmentioning
confidence: 99%
“…We identified 11 trials reporting dyspeptic symptoms in patients receiving coxibs versus NSAID NS (10,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). A previous meta-analysis of these trials calculated a pooled risk reduction of 23% for coxibs versus NSAID NS (12).…”
mentioning
confidence: 99%